1989
DOI: 10.1093/oxfordjournals.eurheartj.a059415
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate and metabolic response to competitive squash in veteran players: identification of risk factors for sudden cardiac death

Abstract: We studied 10 older males during a competitive game and the early post-exercise period to define the metabolic response to squash in veteran players. For comparison, all subjects were also studied during exhaustive treadmill exercise. Squash caused a dramatic increase in heart rate (150%), and circulating levels of noradrenaline (164%), adrenaline (93%), lactate (202%) and free fatty acids (67%). These effects were independent of haemoconcentration. The early post-exercise period (5 min) was characterized by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 1 publication
3
8
0
1
Order By: Relevance
“…The glu cose-containing solutions had significant ef fects only on blood glucose levels following squash, causing significant elevations at 15 and 30 min following the game. The increases in lactate, free fatty acids and glucose with concomitant hypokalaemia in the postexer cise period, previously demonstrated by Bra dy et al [2], have been confirmed in this study. We have also demonstrated that de spite these metabolic changes, indicators of dehydration such as plasma osmolality and plasma sodium are not elevated in the early postexercise period, and that these subse quently fall to values below baseline up to 1 h after the game.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The glu cose-containing solutions had significant ef fects only on blood glucose levels following squash, causing significant elevations at 15 and 30 min following the game. The increases in lactate, free fatty acids and glucose with concomitant hypokalaemia in the postexer cise period, previously demonstrated by Bra dy et al [2], have been confirmed in this study. We have also demonstrated that de spite these metabolic changes, indicators of dehydration such as plasma osmolality and plasma sodium are not elevated in the early postexercise period, and that these subse quently fall to values below baseline up to 1 h after the game.…”
Section: Discussionsupporting
confidence: 91%
“…The observed changes have been postu lated to contribute to arrhythmias and sudden death in older men playing squash [2,3], Hypokalaemia can trigger arrhythmias in nor mal and ischaemic myocardium [6,7]. Free fatty acids have been implicated in the patho genesis of myocardial ischaemia and ventric ular arrhythmias in patients with coronary artery stenosis [8.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations